TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PENIMBANGAN JUAL BELI SEMBAK DI PASAR RENTENG PRAYA KABUPATEN LOMBOK TENGAH - Baiq Fitri Sulastri; Teti Indrawati Purnamasari; Ahmad Saifulhaq Almuhtadi (Universitas Islam Negeri Mataram, 2021)
Justice in buying and selling transactions must be upheld so as not to harm other parties. A seller is obliged not to measure with two measures or weigh with two scales, namely one scale is only used for buying, and the other is used for selling. Fraud in scales and measures is often found in trade transactions between sellers and buyers in the market, which unknowingly there are still some irresponsible sellers who reduce the measurements when weighing their merchandise.